Two complete mitochondrial genomes of the barnacle Lepas anatifera Linnaeus, 1758 (Scalpellomorpha, Lepadidae) implying the possibility of cryptic speciation - Xiao-Nie Lin; Li-Sha Hu; Yun-Wei Dong (Mitochondrial DNA. Part B. Resources, 2022)
The barnacle Lepas anatifera Linnaeus, 1758 (Scalpellomorpha, Lepadidae) is a worldwide distributed species. For investigating its genetic diversity in the northwest Pacific, two complete mitochondrial genomes were determined and analyzed. The lengths of the two complete mitogenomes were 15,708 bp and 15,703 bp, respectively. Both of them contained typical 37 genes with an identical order to L. anserifera Linnaeus, 1767 and L. australis Darwin, 1851 mitogenome. Except for ND1 and ND2, 11 protein-coding genes (PCGs) started with an ATN initiation codon (ATA, ATG, ATC, and ATT). Twelve PCGs were terminated with TAA or TAG stop codon, whereas ND1 possessed an incomplete termination codon (T–). Phylogenetic analysis revealed that L. australis and L. anserifera clustered together, and then with L. anatifera. The distinct genetic distances (0.17) based on concatenated sequence of 13 PCGs between the two mitogenomes of L. anatifera suggest the existence of cryptic speciation. Additional samples from multiple localities should be collected and analyzed to deepen the understanding of cryptic diversity within the northwest Pacific.